2016
DOI: 10.1007/s11882-015-0589-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Comorbidities in Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a heterogeneous disorder that creates a significant burden on the healthcare system. It is caused by a combination of inflammatory, environmental, and host factors; however, the precise mechanism of how each factor leads to CRS continues to be a source of debate. Previous data regarding this topic is often inconsistent or of lower quality. In this article, we review the recent literature on the risk factors and comorbidities in CRS. Large population-based studies have helped est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 74 publications
2
36
1
2
Order By: Relevance
“…24,25 Future studies are needed to investigate whether the increased risk of OSA in the setting of CRS is linked to any of these genetic alterations. Furthermore, other lifestyle risk factors for OSA, such as smoking, 26,27 which is also a major risk factor for CRS 28 and is more commonly practiced and sustained into adulthood among African Americans, 29 might be playing a role in this increased risk. The burden of sleep symptoms and risk of hypertension in the setting of OSA is higher among African Americans compared with other races.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Future studies are needed to investigate whether the increased risk of OSA in the setting of CRS is linked to any of these genetic alterations. Furthermore, other lifestyle risk factors for OSA, such as smoking, 26,27 which is also a major risk factor for CRS 28 and is more commonly practiced and sustained into adulthood among African Americans, 29 might be playing a role in this increased risk. The burden of sleep symptoms and risk of hypertension in the setting of OSA is higher among African Americans compared with other races.…”
Section: Discussionmentioning
confidence: 99%
“…CRS is a multifactorial inflammatory disease with influence from genetic, environmental, and host factors . Typically, surgical treatment, predominantly ESS, is offered when medical therapy with trials of antibiotics and/or nasal and systemic steroids fails, or if complications occur or are suspected.…”
mentioning
confidence: 99%
“…Additionally, Bhattacharyya found that improvement in air quality was associated with a decrease in the prevalence of sinusitis 16. Cigarette smoking has also been linked to an increased risk of CRS,17 although ever smoking was not associated with CRS in our study population.…”
Section: Discussionmentioning
confidence: 48%